Методи синтезу якісних регуляторів для нелінійних динамічних систем - Glazok, O. M. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
Several methods of solving the task of synthesys of quality regulators for a nonlinear dynamic system with polynomial right-hand member of equation are offered. A modified quadratic quality functional with the integrand including components from the expression for the Lyapunov function is used.